NILAI INFORMASI DALAM KOMUNIKASI BENCANA UNTUK PENCEGAHAN DAN PENANGGULANGAN - Fitriawati, Diny (KOMUNIKA BANGSA, 2025)
Entering the third month of 2025, a series of disaster tragedies filled the entire media space. The events beat other events that occurred at the same time. Routine disasters and have become a ritual every time the beginning of the year are floods and similar tragedies as part of the same cause as floods and landslides. Like a cassette that is played every year, the flood song is always heard loudly. But then it disappears along with the season which then changes to the dry season. On that basis, this study aims to determine the role and position of disaster communication which includes a series of efforts in disaster prevention, management and recovery. The research method used is qualitative. The results of the study show that disaster communication carried out by communicators has a significant role in disaster prevention and management and post-disaster. Prevention is not directed so that disasters do not occur immediately but rather prevent losses that will be suffered by disaster victims.